Pengaruh Penerapan Model Pembelajaran ROPES (Review, Overview, Presentation, Exercise, Summary) disertai Pengajaran Terarah Terhadap Pemahaman Konsep Matematis Siswa Kelas VIII SMPN 3 Payakumbuh - Steffiyo, Steffiyo; Zulfaneti, Zulfaneti; Febriana, Rina (STKIP PGRI Sumbar, 2013)
This research is based by the comprehension of students are low so that the result of studentâs mathematics results are below minimum completeness criteria, lacking of student motivation in learning process, and learning is centered on the teacher. The purpose of this study was to determine whether students comprehension of mathematical concepts by applying ROPES instructional model teaching using guided teaching better than an comprehension of mathematical concepts with conventional teaching students in class VIII SMP 3 Payakumbuh. This research is experimental research. The population is a student from class VIII SMP 3 Payakumbuh Academic Year 2013/2014 consisting of 6 classes. The techniques of sample collection taken by randomly. The instrument that used was a test student comprehension of mathematical concepts in the form of an essay test with the reliability of the test r11 = 0,813. The result of hypothesis test obtained Â and Â because the Â more than Â then the hypothesis in this research received. In conclusion, studentâs comprehension of math concept that apply active learning ROPES instructional model teaching using guided teaching is better than conventional learning.